Pengaruh Latihan Push Up dan Dumbbell Lateral Raise terhadap Kekuatan Otot Lengan Atlet - Arif Budiani, Dias; Riski Adi Wijaya, M; Tresnowati, Idah; Widya Putri, Mega; Yusuf, Jamaludin (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This study aims to determine whether there is an effect of push-up and dumbbell lateral raise exercises on the arm muscle strength of athletes from the Nun Archery PanahMu Club in Batang. This research is an experimental study or quantitative research. The population in this study consisted of 10 athletes from the Nun Archery PanahMu Club in Batang. The sampling technique used was purposive sampling. The sample in this study consisted of 10 athletes from the Nun Archery PanahMu Club in Batang. The results of this study indicate that: (1) The first hypothesis, which states that there is an effect of push-up exercises on the arm muscle strength of athletes from the Nun Archery PanahMu Club in Batang, was supported with a significance value of 0.021 < 0.05. (2) The second hypothesis, which states that there is an effect of dumbbell lateral raise exercises on the arm muscle strength of athletes from the Nun Archery PanahMu Club in Batang, was supported with a significance value of 0.022 < 0.05. (3) The third hypothesis, which states that there is a difference in the effect between push-up exercises and dumbbell lateral raise exercises on the arm muscle strength of archery athletes from the Nun Archery PanahMu Club in Batang, was also supported. The results showed that push-up exercises had a greater effect compared to dumbbell lateral raise exercises in improving the arm muscle strength of the athletes from the Nun Archery PanahMu Club in Batang.